Understanding the Role of the Public Employment Agency - Christian Holzner; Makoto Watanabe (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
The Public Employment Agency (PEA) provides intermediation services in the labor market. We investigate the implications of having such an additional market place using a tractable search model. The intermediation services enable registered firms to pay lower wages compared to the private market. Paying lower wages leads to adverse selection. When deciding whether or not to register with the PEA firms have to trade off the negative selection of applicants coming through the PEA with the lower wages possible at the PEA. This explains why only a fraction of firms use the PEA as search channel although it is free of charge. Our model also suggests which job-types are more likely to be registered with the PEA. We test these theoretical predictions empirically using the German Job Vacancy Survey and the German Socio Economic Panel and find strong support for them.
Keywords: J6; 330; Intermediation; Public Employment Agency; Labor Search